DNA and redox state induced conformational changes in the DNA-binding domain of the Myb oncoprotein. - Myrset, A H (1993)
The DNA-binding domain of the oncoprotein Myb comprises three imperfect repeats, R1, R2 and R3. Only R2 and R3 are required for sequence-specific DNA-binding. Both are assumed to contain helix-turn-helix (HTH)-related motifs, but multidimensional heteronuclear NMR spectroscopy revealed a disordered structure in R2 where the second HTH helix was predicted [Jamin et al. (1993) Eur. J. Biochem., 216, 147-154]. We propose that the disordered region folds into a 'recognition' helix and generates a full HTH-related motif upon binding to DNA. This would move Cys43 into the hydrophobic core of R2. We observed that Cys43 was accessible to N-ethylmaleimide alkylation in the free protein, but inaccessible in the DNA complex. Mutant proteins with charged (C43D) or polar (C43S) side chains in position 43 bound DNA with reduced affinity, while hydrophobic replacements (C43A, C43V and C43I) gave unaltered or improved DNA-binding. Specific DNA-binding enhanced protease resistance dramatically. Fluorescence emission spectra and quenching experiments supported a DNA-induced conformational change. Moreover, reversible oxidation of Cys43 had an effect similar to the inactivating C43D mutation. The highly oxidizable Cys43 could function as a molecular sensor for a redox regulatory mechanism turning specific DNA-binding on or off by controlling the DNA-induced conformational change in R2.